Development Opportunities For Venname Shrimp Farming In East Nusa Tenggara: A Prospective Analysis - Franchy Christian Liufeto; Ade Yulita Hesti Lukas; Wesly Pasaribu (Publikasi Indonesia, 2023)
The research examines opportunities in the dvlopment of venname shrimp cultivation which is one of the main commodities in the pond cultivation business, but there are still many problems facd by farmers in the venname shrimp cultivation development business. The purpose of this research is to find out the effortsand priority strategies that can be applied in developing the venname shrimp business in East Nusa Tenggara. The results that the main opportunity in developing the vennam shrip business is a dafe and controlled environment. While the biggest threat is the price of venname shrimp from other areas which is cheaper. The priority strategy that can b applied to efforts in developing venname shrimp cultivation businesses is by maintaining the quality, promotion of fisheries, venname shrimp distribution networks, partnerships, and private investment to redeem the export market, optimizing empowerment, increasing the number of seeding units and improving the infrastructure facilities for the cultivation site as well as improving the quality of farmers’ resources technically, morally and spiritually throungh coaching activities to maximize the production and competitiveness of venname shrimp.